Sex-Dependent Effects on Liver Inflammation and Gut Microbial Dysbiosis After Continuous Developmental Exposure to Trichloroethylene in Autoimmune-Prone Mice - Blossom, Sarah J.; Gokulan, Kuppan; Arnold, Matthew; Khare, Sangeeta (Frontiers in Pharmacology, 2020)
Trichloroethylene (TCE) is a common environmental toxicant linked with hypersensitivity and autoimmune responses in humans and animal models. While autoimmune diseases are more common in females, mechanisms behind this disparity are not clear. Recent evidence suggests that autoimmunity may be increasing in males, and occupational studies have shown that TCE-mediated hypersensitivity responses occur just as often in males. Previous experimental studies in autoimmune-prone MRL+/+ mice have focused on responses in females. However, it is important to include both males and females in order to better understand sex-disparity in autoimmune disease. In addition, because of an alarming increase in autoimmunity in adolescents, developmental and/or early life exposures to immune-enhancing environmental pollutants should also be considered. Using MRL+/+ mice, we hypothesized that TCE would alter markers related to autoimmunity to a greater degree in female mice relative to male mice, and that TCE would enhance these effects. Mice were continuously exposed to either TCE or vehicle beginning at gestation, continuing during lactation, and directly in the drinking water. Both male and female mice were evaluated at 7 weeks of age. Sex-specific effects were evident. Female mice were more likely than males to show enhanced CD4+ T cell cytokine responses (e.g., IL-4 and IFN-). Although none of the animals developed pathological or serological signs of autoimmune hepatitis-like disease, TCE-exposed female mice were more likely than males in either group to express higher levels of biomarkers in the liver related to regeneration/repair and proliferation. Levels of bacterial populations in the intestinal ileum were also altered by TCE exposure and were more prominent in females as compared to males. Thus, our expectations were correct in that young adult female mice developmentally exposed to TCE were more likely to exhibit alterations in immunological and gut/liver endpoints compared to male mice.